Pharmacology and the Nursing Role in Combating Antibiotic Resistance: A Comprehensive Review - ALANAZI, AREEJ MAHAJA; ALQAHTANI, MOHAMMAD SAAD MOHAMMAD; ALOTABI, SHAYEEAA FAEH; AL OTAIBI , TAHANI SUAD; ALJASER, MESHAL ABDULLAH OMAR; HANTOOL, DAWLAT IBRAHIM; SULAIS, ABEER ALI; ALSOFYANI, NAJLAA MOHAMMED; AL OUF, MARIAM ABDULWAHAB SALEH; ALMASKEEN, HUSSAIN MOHAMMED; et al. (Journal of Posthumanism, 2024)
Antibiotics represent one of the most significant breakthroughs in modern pharmacology, drastically reducing morbidity and mortality associated with infectious diseases. Their discovery revolutionized medical practice, making once-deadly bacterial infections curable and preventable. From penicillin to broad-spectrum antimicrobials, their role has been central to public health advancements. However, the effectiveness of these drugs depends heavily on proper pharmacological application, including correct dosing, selection, and adherence. Nurses, as frontline healthcare providers, play a vital role in ensuring these principles are upheld, especially in the context of antibiotic stewardship.